Peningkatan Literasi Numerik melalui Pengenalan Aplikasi Perhitungan Bilangan Prima, Ganjil, dan Genap di Kalangan Pelajar SMK Bina Sriwijaya Palembang menggunakan Microsoft Visual Basic 6.0 - Munawaroh, Faridatul; Aqil, Ibnu; Triana, Dora Indah; Sulastri, Asiawatie (Faculty of Engineering University of Pahlawan Tuanku Tambusai, 2025)
The development of information technology provides an opportunity to create innovation in the world of education, especially in supporting the calculation process that is often carried out by teachers, students, and education personnel. One solution that can be implemented is the development of the